Introduction to cybercrime: computer crimes, laws, and policing in the 21st century - Hill, Joshua B. (Praeger security international textbook, 2016)
"Explaining cybercrime in a highly networked world, this book provides a comprehensive yet accessible summary of the history, modern developments, and efforts to combat cybercrime in various forms at all levels of government--international, national, state, and local. Provides accessible, comprehensive coverage of a complex topic that encompasses identity theft to copyright infringement written for non-technical readers Pays due attention to important elements of cybercrime that have been largely ignored in the field, especially politics Supplies examinations of both the domestic and international efforts to combat cybercrime Serves an ideal text for first-year undergraduate students in criminal justice programs"--